Investigating the impact of platelet transfusions on adverse outcomes in patients with thrombotic thrombocytopenic purpura: A systematic review of published studies - Clerici, Bianca; Tarasconi, Elisa; Benedetto, Chiara; Pisetta, Chiara; Birocchi, Simone; Podda, Gian Marco (Thrombosis research, 2025)
•Whether platelet transfusions are harmful to TTP patients is currently unclear.•To address this gap, we carried out a systematic review, retrieving 11 eligible studies.•We found that the all-cause mortality of transfused patients was significantly higher compared to non-transfused patients.•There were no significant differences in the rates of other target organ complications.•Our results could signify harm of platelet transfusions or a greater disease severity of transfused TTP patients.